TABELA AND FISH FARMING ARE LOCAL WISDOMS ETHNIC SUMATERA FOR SUPPORTED ON SUSTAINABLE AGRICULTURE IN NORTH SUMATERA, INDONESIA - Ameilia Zuliyanti Siregar (Jurnal Pertanian Tropik, 2017)
Direct seeding (Tabela) and fish farming (Minapadi), traditional methods used for producepaddy plantation and animal proteins for sustainable food security in Northern Sumatra weredone. This study was conducted using a combination of methods to the study of literature(data collectively in USU Library and library of USM) and observations in the fields (lowlandand terrace from Langkat district and Smalungun district were conducted since December2016 to March 2017. As much as two types of rice crops (Ciherang and IR 64) are cultivatedshowed the status (prey and predator) of insects in Langkat and Simalungun districtsrespectively. Direct Seed (Tabela) in Langkat agroecosystems applied to irrigated rice, rainfed andtidal land is an alternative model of technology and integrated crop management approach isenvironmentally friendly. Besides, fish farming (Minapadi) was done in Simalungun districtconsumed by the family farmers and partly as sold as additional revenue. The problems areidentified from Tabela and Minapadi farmers in Langkat and Simalungun, consist of technologyadvice is difficult; do not answer problems; innovation technology creates new problems forfarmers due to lack of appropriate with the socio-economic-culture;application of technology requires a high cost while remuneration derived less adequate;systems and counseling strategies are still weak so not able to convey the message properly;indifference farmers to offer new technologies; the existence of uncertainty in control ofresources. Food security system with integrated farming through seeded fields and fish farmingthe concept on three of the management, such as integrated crop management, integrated pestmanagement and integrated nutrient management based on local knowledge should be cultivatedand preserved in Indonesia. The importance of communication, improve interpretation andknowledge of paddy farmers, the adoption of technology and infrastructure empowerment inagriculture, especially in North of Sumatera was increasing the productivity of rice farmers inNorthern Sumatra.